2017
DOI: 10.1021/acs.jcim.6b00601
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Embedding of Attributed Molecular Graphs for Physical Property Prediction

Abstract: The task of learning an expressive molecular representation is central to developing quantitative structure-activity and property relationships. Traditional approaches rely on group additivity rules, empirical measurements or parameters, or generation of thousands of descriptors. In this paper, we employ a convolutional neural network for this embedding task by treating molecules as undirected graphs with attributed nodes and edges. Simple atom and bond attributes are used to construct atom-specific feature ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
374
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(377 citation statements)
references
References 53 publications
1
374
0
2
Order By: Relevance
“…In particular, they have achieved a remarkable performance in classifying documents in citation networks 39 , modeling and predicting chemical properties of molecules 40,41,67 and protein interface prediction with applications in drug discovery and design 42 . Here, we propose our model based on the work of Kipf & Welling 39 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they have achieved a remarkable performance in classifying documents in citation networks 39 , modeling and predicting chemical properties of molecules 40,41,67 and protein interface prediction with applications in drug discovery and design 42 . Here, we propose our model based on the work of Kipf & Welling 39 .…”
Section: Methodsmentioning
confidence: 99%
“…More recently, geometric deep learning methods 37 and more specifically Graph Convolutional Networks (GCNs) 38,39 have offered a way to overcome these limitations by generalizing convolutional operations on more natural graph-like molecular representations. Graph Convolutional Networks have shown tremendous success in various problems ranging from learning useful molecular fingerprints 40 , to predicting biochemical activity of drugs 41 , to protein interface prediction 42 .…”
mentioning
confidence: 99%
“…They update node-level representations based on the neighbourhood, and compute a graph-level representations (molecule representations, in our case) based on all nodes representations. We will call the "minimal" formulation of GNN, the intuitive and simple encoding of the graph in which the AGGREGATE (l) graph function is defined by the sum of all nodes representations, at each layer [28,29,[32][33][34][35]:…”
Section: Molecular Graph Encodermentioning
confidence: 99%
“…We focused on well-established machine learning models instead of more recent deep learning models, such as graph-based neural networks. 36,[64][65][66][67] This is because our main goal was to investigate the virtual screening principles for choosing the best model for a specific task (PriA-SSB AS) in a practical setting instead of broadly benchmarking virtual screening algorithms. In addition, a recent benchmark showed that conventional methods outperformed graph-based methods on most biophysics datasets.…”
Section: Discussionmentioning
confidence: 99%